Respuesta :
Answer:
infinite solutions
Step-by-step explanation:
Given
- 6(n - 8) = 4(12 - 5n) + 14n ← distribute parenthesis on both sides
- 6n + 48 = 48 - 20n + 14n, that is
- 6n + 48 = 48 - 6n ( add 6n to both sides )
48 = 48 ← True
This indicates that the equation is true for any value of n
Answer:
This is a very classical type of equation in which, the solution is basically any number and it is known as an "Identity". So it has infinite solutions
Step-by-step explanation:
- Apply the distributive law to both sides of the equation:
-6(n-8) = 4(12-5n)+14n
-6n-6*(-8) = 4*12+4*(-5n) + 14n
- Reduce similar terms
-6n+48=48-20n+14n
-6n+48=48-6n
- From here it is clear them to see that by adding -48 and 6n to both sides one obtains the identity 0 = 0
-6n+48=48-6n
-6n +6n + 48 -48 = 48 -48 - 6n + 6n
0 = 0
- So every time you find this kind of problem and after reducen the equation you end up with a true statement, then the equation has infinite solutions